Technological Aspects and Environmental Consequences of Mining Encryption - Makurin, Andrii (Dr. Viktor Koval, 2023)
Introduction. The digital economy has significantly changed not only the types, forms and mechanism of payments, but also the form of money itself. Electronic money is becoming more popular, which increases the relevance and importance of the study of technical aspects and environmental consequences of mining encryption. The choice of equipment for cryptocurrency mining and its impact on the environment remains a rather debatable issue. It is also not clear how to calculate the costs of mining cryptocurrencies in order to determine the cost of such coins which creates obstacles to the normal reflection in the accounting of such activities in the future and the payment of the corresponding taxes on such operations where cryptocurrencies are involved. Aim and tasks. The study aims is to investigate modern approaches to cryptocurrency mining and the characteristics of the mining process itself, as well as the selection of the main equipment and a list of costs to ensure this activity takes into account the environmental consequences of mining encryption. Results. Cryptocurrency mining is the process of creating digital currencies. All transactions in the network are not processed by any central authority, but by any user connected to the network. The creation of cryptocurrency, i.e. its emission, is the acquisition of certain property rights. Determining the cost of mining, for example, one bitcoin depends on the amount of resources spent: the depreciation of the equipment that was used to generate new blockchain blocks and the monthly costs of its maintenance, the cost of high-speed Internet service, the configuration of the mining software product on a   particular pool, combined electricity costs. Conclusions. The development of the cryptocurrency market has both positive and negative consequences at the micro and macro levels. Advantages include independence from the state-regulated banking system and general accessibility; high economic efficiency of mining; transparency of transactions, confidentiality and anonymity, security of data owners; high data security against external influences and attacks; absence of time or territorial restrictions; general availability and lack of need to create centralized data repositories; effective mechanism against theft, counterfeiting and inflation, irreversible nature of transactions. At the macro level, the advantages are the high capitalization of cryptocurrencies, which can contribute to meeting the financial needs of the state as a whole and independence from the state. Therefore, further accounting of such a specific asset as cryptocurrency requires detailed research.